Risk Management And Its Impact On Company Value - Suharti, Eni; Hakim, Luqman; Akbar, Maulana (DINASTI RESEARCH, 2024)
Determining the impact of business risks (DOL), financial risk (DFL) and market risk (NIM) on the value of the businesses of banks that are Listed with the Stock Exchange of Indonesia, the period used in this research is 4 (four) years, namely from from 2019-2022. The methodology for this investigation is quantitative. 45 banking businesses that were listed between 2019 and 2022 on the Indonesia Stock Exchange comprised the study's population. Purposive sampling was the method employed for the sample, and ten firms were included in the sample. Panel data regression analysis is the data analysis method employed, and Eviews 12 is used to facilitate the process. The results of the research show that partially business risk (DOL) has an effect on company value, a high DOL value indicates that the company has experienced a decrease in its business risk so that it can increase company value. The financial risk variable (DFL) and market risk variable (NIM) partially have no effect on company value. Simultaneously business risk (DOL), financial risk (DFL) and market risk (NIM) have a positive and significant effect on company value in the 2019-2022 period